Nicolás Guillén y la Guerra Civil española (Periphērica, 2022)
The poetry that emerges from the Spanish Civil War (1936-1939) develops a poetic discourse, to motivate its readers to become active historical agents and witnesses, and to politically support the Republican cause. In España: Poema en cuatro angustias y una esperanza (Spain: Poem in Four Anguishes and One Hope) the Cuban poet Nicolás Guillén (1902-1989) defends a poetics of solidarity with Republican Spain, while also acknowledging the colonial and postcolonial history that problematizes this “transatlantic” aesthetic position. Particularly in the “Angustia primera” and in the last poem “La voz de la esperanza,” Guillén highlights the racial and cultural identity of the speaker to legitimize his solidarity with the Republican cause from the perspective of the Latin American subject, who feels their cultural roots and political convictions connects them to Spain. The four “anguishes” or poems reveal the Latin American alliance with anti-fascist Spain and lament the tragedy of the death of Federico García Lorca, while the last poem defiantly and optimistically underlines the ethical imperative to fight against fascism. In this essay, I analyze España: Poema en cuatro angustias y una esperanza by Guillén within the political, literary, and cultural context, of an avant-garde poetics and as part of his intellectual effort to support with his prose, especially his chronicles, the Republican cause. La poesía que emerge de la Guerra Civil española (1936-1939) desarrolla un discurso poético para motivar a sus lectores a que se conviertan en activos testigos históricos. En España: Poema en cuatro angustias y una esperanza, el poeta cubano Nicolás Guillén (1902-1989) defiende una poética de la solidaridad con la España republicana pero consciente de la historia colonial y postcolonial que problematiza esta postura estética “transatlántica”. En particular en la “Angustia primera” y en el último poema, “La voz de la esperanza”, Guillén resalta la identidad racial y cultural de la voz poética para legitimar la solidaridad con la causa republicana desde la perspectiva del latinoamericano unido al español por sus raíces culturales y sus convicciones políticas. Las cuatro angustias revelan la alianza latinoamericana con la España antifascista y lamentan la tragedia ante la muerte de Federico García Lorca, mientras que el último poema, subraya con actitud desafiante y optimista el imperativo ético de luchar contra el fascismo. En este ensayo, principalmente analizo España: Poema en cuatro angustias y una esperanza de Guillén dentro del contexto político, literario y cultural de la poética vanguardista, y como parte de su esfuerzo intelectual al apoyar con su prosa, en especial con sus crónicas, la causa republicana.